Board attributes and performance of government-linked companies (GLCs): evidence from an emerging economy - Sheikh Hassan, Ahmad Fahmi; Karbhari, Yusuf; Mohamad Isa, Ahmad Afendi; Ab Razak, Nazrul Hisyam (Virtus Interpress, 2017)
Government linked companies (GLCs) play a unique role in the Malaysian public sector and are perceived to be the key drivers of the economy wielding influence in the financial market. This study investigates the impact of an important governance mechanism, i.e. the board of directors on performance of 32 Malaysian listed GLCs for the period 2008 to 2013. The board attributes examined include board size, board structure, board independence, board competence, board meetings and directors’ equity ownership. The three proxies of financial performance employed are return on assets (ROA), return on equity (ROE) and earnings per share (EPS) with firm size and leverage being used as control variables. We find board size to have a positive but insignificant relationship with ROA whilst board structure, board independence and board competence indicate a positive relationship with ROE. Board competence also shows a positive relationship with EPS. However, board independence and directors equity ownership report a significant inverse relationship with ROA. A possible explanation is that independence and controlling stake of the board could not influence board strategy formulation and business decisions as government maintains full authority and final say on matters. Overall, the study contributes to the growing body of literature especially relating to Government linked companies.